Phase structure and tensile creep of recycled poly(ethylene terephthalate)/short glass fibers/impact modifier ternary composites (eXPRESS Polymer Letters)
Binary and ternary composites of recycled poly(ethylene terephtalate) (rPET), short glass fibres (SGF) and/or impact modifier (IM) were prepared by melt compounding and injection moulding. SEM images of rPET/IM fracture surfaces indicated that IM particles of about 1–2 µm in diameter were uniformly distributed in the rPET matrix, but with a poor adhesion level. Microphotographs of PET/SGF composites evidenced brittle fracture proceeding through the matrix and strong adhesion between components. In ternary composites SGF were evenly distributed, while IM particles were no longer detectable. Tensile creep of rPET and prepared composites was investigated under short and long term testing conditions at various stress levels. Main part of the tensile creep corresponded to the elastic time-independent component, while the timedependent component was rather limited even at relatively high stresses. While SGF accounted for a significant decrease in the overall creep compliance, the incorporation of IM induced a small decrease in the compliance and a non-linear viscoelastic behavior. In ternary composites, the reinforcing effects of SGF was dominating. Under a constant stress, the logarithm of compliance grew linearly with the logarithm of time. The creep rate, which resulted to be generally very small for all tested materials, was slightly reduced by SGF and increased by IM.